Analisis Faktor yang Berpengaruh terhadap Tingkat Pendapatan Perempuan Pedagang Pakaian di Pasar Induk Tabanan - Ni Made Ari Cahyani; Ni Luh Karmini (Journal Of Business, Finance, and Economics (JBFE), 2024)
The role of women is very essential for the continuity of development, because they are able to support increasing social and economic capacity in society. This research uses variables, namely working capital, working hours, length of business and education and income level. This research aims to analyze the simultaneous and partial influence of working capital, working hours, length of business and level of education on the income level of women clothing traders at the Tabanan Main Market. The sample size in this study used a saturated sample with the sample data reaching 98 women who work as clothing traders. In carrying out the sample determination process, the researchers applied a non-probability sampling technique using saturated sampling. The methods used in data collection activities include observation activities, structured interviews and also conducting in-depth interviews. In this research, data techniques have been used in the form of descriptive analysis and also multiple linear regression analysis. Based on the research results found, the variables of working capital, working hours, length of business and education simultaneously have a significant effect on the income of women clothing traders at the Tabanan Main Market. The variables working capital, working hours, length of business and education partially have a positive and significant effect on the income of women clothing traders at Tabanan Main Market.